2019
DOI: 10.1177/2325958218824310
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Treatment Supporters and Patients Starting HIV Therapy in Lima, Peru

Abstract: As per the National HIV Program in Peru, the designation of a patient-elected treatment supporter is a requisite for starting antiretroviral therapy (ART). These individuals are expected to aid the patient in medical and social support. This qualitative study examines the interaction between treatment supporters and people living with HIV/AIDS (PLWHA) to elucidate key dynamics contributing to care. Twenty individual interviews with treatment supporters were analyzed alongside 5 group interviews: 2 groups of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The common suggestions put forward by the male and female gender on ways to address nonadherence to HIV/AIDS management which mainly focused on personal efforts of PLWHA, support from family members and healthcare personnel are consistent with studies carried out in Nigeria. 15,23,38 The recommendations made by the female gender which mainly focused on encouraging disclosure of retroviral status to trusted friend/relative who also may serve as a treatment supporter(s) have also been documented in previous studies carried out in Nigeria, 45 Uganda, 46,47 Peru, 48 Puerto Rico, 49 and United States. 49 Furthermore, contributions made by the male gender on attending adherence counselling and using patients as whistleblowers will help the standard of operations within the treatment centre as healthcare providers will treat patients with empathy, noting that there are sanctions for misconduct.…”
Section: Discussionmentioning
confidence: 83%
“…The common suggestions put forward by the male and female gender on ways to address nonadherence to HIV/AIDS management which mainly focused on personal efforts of PLWHA, support from family members and healthcare personnel are consistent with studies carried out in Nigeria. 15,23,38 The recommendations made by the female gender which mainly focused on encouraging disclosure of retroviral status to trusted friend/relative who also may serve as a treatment supporter(s) have also been documented in previous studies carried out in Nigeria, 45 Uganda, 46,47 Peru, 48 Puerto Rico, 49 and United States. 49 Furthermore, contributions made by the male gender on attending adherence counselling and using patients as whistleblowers will help the standard of operations within the treatment centre as healthcare providers will treat patients with empathy, noting that there are sanctions for misconduct.…”
Section: Discussionmentioning
confidence: 83%
“…A 2016 cross-sectional study found a high-level of stigma was associated with HIV, which was negatively associated with ART adherence [27]. A 2019 study showed that patient-elected treatment supporters helped people living with HIV take responsibility for their treatment, facilitated transfer of knowledge and provided emotional support for patients in Lima [28]. A recent longitudinal study has identified the need for pre-diagnosis psychological assessment in Peruvian men who have sex with men to identify those with maladaptive coping pre-diagnosis who are less likely to link to care [29].…”
Section: Introductionmentioning
confidence: 99%
“…A 2016 cross-sectional study found a high-level of stigma was associated with HIV, which was negatively associated with ART adherence (29). A 2019 study showed that patientelected treatment supporters helped people living with HIV take responsibility for their treatment, facilitated transfer of knowledge and provided emotional support for patients in Lima (30). A recent longitudinal study has identified the need for pre-diagnosis psychological assessment in Peruvian men who have sex with men to identify those with maladaptive coping pre-diagnosis who are less likely to link to care (31).…”
Section: Introductionmentioning
confidence: 99%